A measurement‐based study on user management in private BitTorrent communities. (5th July 2012) - Jiang, Honglei; Jin, Hai; Guo, Song; Liao, Xiaofei
SUMMARY: Beyond the traditional BitTorrent, a new genre of peer‐to‐peer communications protocol for worldwide file sharing is rapidly evolving towards private BitTorrent (PT). In recent years, a proliferation of PT communities have emerged. To enhance the user experience, account‐based share‐ratio enforcement (SRE) has been developed and widely adopted. Whereas existing studies mainly take SRE as an incentive, we discover that it also plays a critical role in selecting and filtering users. In addition to SRE, a rich set of user management rules, such as registration management, banning policies, and user caste system, are also studied in this paper. This includes to explore their effects on user behavior, download performance, content availability, and system scalability. The measurement results presented in this paper are based on large‐scale experiments conducted over six representative PT sites for over a year. We find that the stricter registration will lead to fewer new users, resulting in a scalability problem, which is critical for the PT communities because the download performance and content availability depend on not only the contribution of users but also the population of the community. Our measurement and analysis pose a direction for the design of new incentive mechanisms that take the difficulty of enrollment into the consideration.Copyright © 2012 John Wiley & Sons, Ltd.